New Technologies for Cultural Heritage Documentation and Conservation: The Role of Geomatics - Tucci, Grazia; Bonora, Valentina (ICONARCH International Congress of Architecture and Planning, 2012)
The concept of Cultural Heritage is rapidly evolving, connoting the union of an intrinsic and an extrinsic value that includes several economic, territorial, environmental, academic and social aspects. The terrible natura! disasters ( cyclones, cloudbursts, floods, landslides, volcanic eruptions and earthquakes) that periodically occur weaken our fragile cultural heritage, which is constantly exposed to risk factors. Failing to protect it has negative effects on the sectors mentioned above, as we know that far some of these phenomena the anthropic action (i.e. pollution, improper use) actively contributed to their occurrence. In compliance with this wider view, the scientific and technological research is acting in different fields: from chemical, physical and biological sciences to nanosciences, from the methods of spatial positioning to info sciences.